Structure and Function of PilQ, a Secretin of the DNA Transporter from the Thermophilic Bacterium Thermus thermophilus HB27 - Burkhardt, Janin (American Society for Biochemistry and Molecular Biology, 2011)
Secretins are a family of large bacterial outer membrane protein complexes mediating the transport of complex structures, such as type IV pili, DNA and filamentous phage, or various proteins, such as extracellular enzymes and pathogenicity determinants. PilQ of the thermophilic bacterium Thermus thermophilus HB27 is a member of the secretin family required for natural transformation. Here we report the isolation, structural, and functional analyses of a unique PilQ from T. thermophilus. Native PAGE, gel filtration chromatography, and electrophoretic mobility shift analyses indicated that PilQ forms a macromolecular homopolymeric complex that binds dsDNA. Electron microscopy showed that the PilQ complex is 15 nm wide and 34 nm long and consists of an extraordinary stable “cone” and “cup” structure and five ring structures with a large central channel. Moreover, the electron microscopic images together with secondary structure analyses combined with structural data of type II protein secretion system and type III protein secretion system secretins suggest that the individual rings are formed by conserved domains of alternating α-helices and β-sheets. The unprecedented length of the PilQ complex correlated well with the distance between the inner and outer membrane of T. thermophilus. Indeed, PilQ was found immunologically in both membranes, indicating that the PilQ complex spans the entire cell periphery of T. thermophilus. This is consistent with the hypothesis that PilQ accommodates a PilA4 comprising pseudopilus mediating DNA transport across the outer membrane and periplasmic space in a single-step process.